2009
DOI: 10.1128/jcm.01643-08
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Implementation of a Chromogenic Agar Medium for Salmonella Detection in Stool in Routine Laboratory Diagnostics

Abstract: We evaluated which chromogenic agar medium for Salmonella detection in stool would be most sensitive and specific in our culture protocol. The use of BBL CHROMagar Salmonella chromogenic medium combined with xylose-lysine-deoxycholate agar yielded a sensitivity of 100% and also reduced workload and costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…There are significant differences at P<0.05 between classical method and PCR results because the percentage of Salmonella spp depend on classical methods has low specificity as compared with PCR. Therefore, there are many false-positive (18,19). This study concluded that the use of PCR technology required only four hours after the primary isolation from Selenite broth.…”
Section: Discussionmentioning
confidence: 85%
“…There are significant differences at P<0.05 between classical method and PCR results because the percentage of Salmonella spp depend on classical methods has low specificity as compared with PCR. Therefore, there are many false-positive (18,19). This study concluded that the use of PCR technology required only four hours after the primary isolation from Selenite broth.…”
Section: Discussionmentioning
confidence: 85%
“…Also, it was confirmed that MSRV medium was significantly better than RV medium in the test of isolation of Salmonella from chicken feces and swan stools, but showed no difference in bovine feces [2]. van Dijk et al [3] compared the isolation rates for Salmonella of XLD and SS media from 1,339 human stool samples, and found that the isolation rate for XLD was higher than that of SS medium. Furthermore, some media are not suitable for the growth of certain serovars of Salmonella [2].…”
Section: Discussionmentioning
confidence: 99%
“…Choosing appropriate enrichment broths and selective media according to animal species is an effective way of increasing the isolation rate of Salmonella. Moreover, to optimize the detective performance of Salmonella, it is necessary to select a variety of separation media and use them in combination [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Biz çalışmamızda klasik besiyerleri ile daha önce karşılaş-tırma çalışmaları yapılmış, güvenilirliğini kanıtlamış bir kromojenik besiyeri olan CHROMagar Salmonella plus besiyerini kullanmayı tercih ettik [23][24][25][26] . Salmonella türü bakterilerin bu besiyerinde yaptıkları tipik koloni görünümü ve rengi (S. Typhi, S. Paratyphi A ve laktoz pozitif Salmonella bu besiyerinde pembe/leylak rengi olarak görülür) nedeni ile ayrıca zaman kaybettirici saflaştırma işlemlerine gerek kalmamaktadır 6 .…”
Section: Maldi-tof'un Başarısı Phoenix Otomatize Cihazı Ileunclassified